Metabolic Rewiring of Kynurenine Pathway during Hepatic Ischemia–Reperfusion Injury Exacerbates Liver Damage by Impairing NAD Homeostasis. Issue 35 (30th October 2022) - Xu, Bowen; Zhang, Peng; Tang, Xiaolong; Wang, Shiguan; Shen, Jing; Zheng, Yuanwen; Gao, Chao; Mi, Ping; Zhang, Cuijuan; Qu, Hui; Li, Shiyang; Yuan, Detian
Abstract: Hepatic ischemia–reperfusion (IR) injury remains a common issue lacking effective strategy and validated pharmacological targets. Here, using an unbiased metabolomics screen, this study finds that following murine hepatic IR, liver 3‐hydroxyanthranilic acid (3‐HAA) and quinolinic acid (QA) decline while kynurenine and kynurenic acid (KYNA) increase. Kynurenine aminotransferases 2, functioning at the key branching point of the kynurenine pathway (KP), is markedly upregulated in hepatocytes during ischemia, shifting the kynurenine metabolic route from 3‐HAA and QA to KYNA synthesis. Defects in QA synthesis impair de novo nicotinamide adenine dinucleotide (NAD) biosynthesis, rendering the hepatocytes relying on the salvage pathway for maintenance of NAD and cellular antioxidant defense. Blocking the salvage pathway following IR by the nicotinamide phosphoribosyltransferase inhibitor FK866 exacerbates liver oxidative damage and enhanced IR susceptibility, which can be rescued by the lipid peroxidation inhibitor Liproxstatin‐1. Notably, nicotinamide mononucleotide administration once following IR effectively boosts NAD and attenuated IR‐induced oxidative stress, inflammation, and cell death in the murine model. Collectively, the findings reveal that metabolic rewiring of the KP partitions it away from NAD synthesis in hepatic IR pathophysiology, and provide proof of concept that NAD augmentation is a promising therapeutic measure for IR‐induced liver injury. Abstract : Kyat2‐mediated metabolic rewiring of the kynurenine pathway partitions it away from de novo nicotinamide adenine dinucleotide (NAD) biosynthesis in hepatic ischemia–reperfusion injury. Single intraperitoneal dose of nicotinamide mononucleotide post‐reperfusion effectively boosts NAD and reduces liver damage, providing proof of concept that replenishing NAD pools may be a promising and low‐cost strategy against hepatic ischemia–reperfusion injury.